2015
DOI: 10.1007/s10546-015-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Weibull Wind-Speed Distribution Parameters Derived from a Combination of Wind-Lidar and Tall-Mast Measurements Over Land, Coastal and Marine Sites

Abstract: Wind-speed observations from tall towers are used in combination with observations up to 600 m in altitude from a Doppler wind lidar to study the long-term conditions over suburban (Hamburg), rural coastal (Høvsøre) and marine (FINO3) sites. The variability in the wind field among the sites is expressed in terms of mean wind speed and Weibull distribution shape-parameter profiles. The consequences of the carrier-to-noise-ratio (CNR) threshold-value choice on the wind-lidar observations are revealed as follows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 33 publications
3
72
0
Order By: Relevance
“…Due to the simplicity and the establishment of common filtering methods, there have been very few studies dealing with the effects of LiDAR filtering to date. The first critical examination of the influence of CNR-filtering on wind speed distributions was presented by Gryning et al [15]. From Gryning et al [15] and Pal et al [10,11], we interpret that LiDAR data filtering based on a rigid CNR-threshold can lead to inaccurate velocity determination.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Due to the simplicity and the establishment of common filtering methods, there have been very few studies dealing with the effects of LiDAR filtering to date. The first critical examination of the influence of CNR-filtering on wind speed distributions was presented by Gryning et al [15]. From Gryning et al [15] and Pal et al [10,11], we interpret that LiDAR data filtering based on a rigid CNR-threshold can lead to inaccurate velocity determination.…”
Section: Introductionmentioning
confidence: 70%
“…The first critical examination of the influence of CNR-filtering on wind speed distributions was presented by Gryning et al [15]. From Gryning et al [15] and Pal et al [10,11], we interpret that LiDAR data filtering based on a rigid CNR-threshold can lead to inaccurate velocity determination. For quality assurance of the measurement data, a variety of filters may be combined to obtain an outlier free data set [16,17].…”
Section: Introductionmentioning
confidence: 70%
“…Doppler lidar measures the mean wind speed with a high and known accuracy; Floors (2013) and Peña et al (2013) found good agreement between wind lidar and cup-anemometer measurements at 100 m for a CNR > −22 dB, with agreement deteriorating as the CNR threshold is lowered (as expected from Figure 2). The relationship between the long-term wind speed and the CNR threshold value is further discussed in Gryning et al (2016). In other words, we can assume U S ≈ U L ≈ U.…”
Section: A New Scaling Methodsology For Lidar Gustsmentioning
confidence: 99%
“…Typically, a threshold of −22 or −23 dB is used as a limit for the accepted uncertainty in the lidar measurements (e.g. Gryning et al, 2016), which corresponds to an uncertainty of about 0.15 m s −1 . The uncertainty is calculated for each radial velocity component separately and propagated into the geographic wind components calculated using the formulations from Päschke et al (2015).…”
Section: Doppler Lidar Data Qualitymentioning
confidence: 99%
“…Slight distortion of wind shear over 400 m above ground level is observed in LIDAR data between the raw data (lines with white circles) and the concurrent data (lines with black circles) which is about 50% of the raw data. In SODAR data, minor difference is shown between the raw and concurrent data below 500 m aboveground where DRR is over 50% [12]. Figure 9 shows the mean wind speed profiles measured using LIDAR (from 10-min data) and SODAR (from 30-min data) for the campaign period, where the data recovery rate (DRR; dashed lines) decreased with increasing altitude.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%